Identifying cortical specific long noncoding RNAs modified by m6A RNA methylation in mouse brains. Issue 11 (2nd November 2021) - Nie, Yanzhen; Tian, Geng.G.; Zhang, Longbin; Lee, Trevor; Zhang, Zhen; Li, Jing; Sun, Tao
ABSTRACT: Proper development of the mammalian cerebral cortex relies on precise gene expression regulation. Increasing evidence shows that cortical development is regulated by both mRNAs and long noncoding RNAs (lncRNAs), which also are modified by N 6 -methyladenosine (m 6 A). Patterns of m 6 A-methylation in lncRNAs in the developing cortex have not been uncovered. Here we reveal differentially expressed lncRNAs and report stage-specific m 6 A-methylation patterns in lncRNAs expressed in mouse embryonic (E) and postnatal (P) cortices using RNA sequencing (RNA-seq) and methylated RNA immunoprecipitation (MeRIP) sequencing. Many lncRNAs show temporal differential expression, and display genic distribution in the genome. Interestingly, we detect temporal-specific m 6 A-methylation with consensus m 6 A motif GGACU in the last exon in most lncRNAs. And m 6 A methylation levels of lncRNAs are positively correlated with the transcript abundance of lncRNAs that have no significantly differential expression in E- and P-stages. Furthermore, the transcript abundance has a positive correlation between the m 6 A genic lncRNAs and their nearest m 6 A methylated mRNAs. Our work reveals a fundamental expression reference of lncRNAs and their nearest mRNAs, and highlights an importance of m 6 A-mediated epitranscriptomic modifications in lncRNAs that are temporally expressed in the developing cortex.